Review of JKN Patient Referral by Pratama Clinic in Depok District - ., Supriadi (KnE Social Sciences, 2018)
The health care system of participants of the National Health Insurance ( JKN) BPJS Health works through stage referrals, where patients must go through primary health care facilities first and if not handled there, then to the secondary facilities. Referral to secondary facilities should indicate that a specialist treatment and diagnostic equipment are required. The behavior of patients requesting immediate referral leads to the accumulation of patients in secondary facilities. This research is qualitative with an aim to get a description of referral percentage and its diagnosis. Data were obtained by interviewing 21 primary (pratama) clinical leaders in Depok. The results of the study showed that the average patient referral to secondary facilities amounted to 11% and the diagnosis was contained in 155 diagnoses of BPJS Health provisions that could be handled in primary facilities. In order to know the factors causing the reference a further research in the field is required. Keywords: referral, pratama clinical